Sustainable Energy Design. Study in Esmeraldas, Ecuador - Lourdes, Ruiz; Damarys, Garcia (International Journal of Advanced Engineering Research and Science, 2020)
Sustainable energy design is particularly challenging in equatorial climates with large tourist populations because of demands on fossil fuels for comfortable indoor temperatures. This study analyzed the relationship between windows buildings, design variables usage during hot tourist periods by life cycle analysis in buildings. A study was conducted in buildings of Esmeraldas, Ecuador. A database was used to reconstruct the local microclimatic variations in MERRA 2 coastal areas, on-site observations were made, and a life cycle analysis using SIMAPRO software was used to process the data. The results revealed that window size and exterior protections from solar energy were important features. These findings contribute to the study of buildings in hot coastal areas that require air conditioning, which could be reduced if bioclimatic designs were used on the exterior walls that are most exposed to solar radiation, implying an adverse internal heat gain. Effective bioclimatic design parameters could be used regarding unprotected buildings on beaches to reduce their energy consumption for air conditioning.